Pocket-creation method facilitates endoscopic submucosal dissection of colorectal laterally spreading tumors, non-granular type - Sakamoto, Hirotsugu; Hayashi, Yoshikazu; Miura, Yoshimasa; Shinozaki, Satoshi; Takahashi, Haruo; Fukuda, Hisashi; Okada, Masahiro; Ino, Yuji; Takezawa, Takahito; Sunada, Keijiro; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy International Open, 2017)
Background and study aims The pocket-creation method (PCM) is a novel strategy for endoscopic submucosal dissection (ESD). The aim of this study is to determine the efficacy of the PCM for colorectal laterally spreading tumors, non-granular type (LST-NG).Patients and methods The records of 126 consecutive patients with colorectal LST-NG who underwent ESD between April 2012 and July 2015 were retrospectively reviewed. Patients were divided into PCM (n = 73) and conventional method (CM) (n = 53) groups.Results The en bloc resection rate in the PCM group was significantly higher than in the CM group (100 % [73/73] vs. 92 % [49/53], P = 0.03). The en bloc resection rate with severe fibrosis was higher in the PCM group than in the CM group (100 % [3/3] vs. 60 % [3/5]). The R0 resection rate for the two groups was not statistically significantly different (93 % [68/73] vs. 91 % [48/53], P = 0.74). The perforation rate in the PCM group was lower than in the CM group although not statistically significantly less (0 % 0/73 vs. 4 % 2/53, P = 0.18). For lesions resected en bloc, dissection speed for the PCM group was significantly faster than for the CM group (median [IQR], 19 [13 –24] vs. 14 [10 – 22] mm2/min, P = 0.03).Conclusion ESD using PCM achieves a reliable and safe resection of colorectal LST-NG.